2015
DOI: 10.7181/acfs.2015.16.2.73
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Prostaglandin E1 and Sildenafil Citrate Administration on Skin Flap Survival in Rats

Abstract: BackgroundAlprostadil and sildenafil are known vasodilators used independently to improve flap survival in animal models. In this study, we investigate whether these agents act synergistically to decrease flap necrosis in rat models.MethodsAfter acclimation period, 4 groups of 10 male white rats were given a modified McFarlane skin flap. The postoperative treatment included saline control (Group A), sildenafil citrate-only (Group B), alprostadil-only (Group C), and both sildenafil and alprostadil (Group D). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…Histological findings related to rats of the control group in the present study revealed the same results of Ayyildiz et al 11 , Choi et al 19 , and Rech et al 20 who showed that the main pathological changes in the skin flap are epidermal exfoliation, widespread neutrophil leukocyte infiltration, increased granulation tissue, increased inflammation, necrosis, and fibroblastic reaction ( Supplementary Fig. 3A).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Histological findings related to rats of the control group in the present study revealed the same results of Ayyildiz et al 11 , Choi et al 19 , and Rech et al 20 who showed that the main pathological changes in the skin flap are epidermal exfoliation, widespread neutrophil leukocyte infiltration, increased granulation tissue, increased inflammation, necrosis, and fibroblastic reaction ( Supplementary Fig. 3A).…”
Section: Discussionsupporting
confidence: 90%
“…8). Choi et al 19 showed the same ameliorative effect of sildenafil according to their histological findings.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Its use in breast surgery is gaining more popularity and it has been shown to reduce mastectomy skin flap necrosis [15]. Application of nitroglycerin ointment or intravenous administration of prostaglandin can promote venous drainage through vasodilation [5,16]. If all methods fail and partial or complete necrosis of the NAC is inevitable, healing by secondary intention may also be used with satisfactory outcomes depending on the patient [17].…”
Section: Discussionmentioning
confidence: 99%